Intoxication by Colchicine in a compounded pharmaceutical formulation - Yano, Helena Miyoco (2008)
The present work relate a case of overdose of colchicine in a capsules of compounded pharmaceutical formulation whose ingestion dose initiated a process of acute gastrointestinal haemorrhage leading the patient to death. Colchicine is a pharmacon of low therapeutical index drug, and the maximum recommended dose for gout treatment in adult is 2.5 mg at the first 24 hours. The remaining non- ingested capsules were analyzed by spectrophotometry, and colchicine amount was determined according to the Brazilian Pharmacopoeia, IV edition. The average dosage was of 47.36 mg, that is, about 20 times higher than the maximum recommended dose. The dosage mistake was evidenced in the medicament prescription, and also in consultation the professional responsible for prescribing the medicine on the part of operator who processed the colchicines formulation.